A grammar of Yauyos Quechua - Shimelman, Aviva (Language Science Press, 2017)
This book presents a synchronic grammar of the southern dialects of Yauyos, an extremely endangered Quechuan language spoken in the Peruvian Andes. As the language is highly synthetic, the grammar focuses principally on morphology; a longer section is dedicated to the language's unusual evidential system. The grammar's 1400 examples are drawn from a 24-hour corpus of transcribed recordings collected in the course of the documentation of the language.
English
Keywords: linguistics; morphology; synchronic grammar; endangered languages; quechuan languages; evidential system of quechua; Clitic; Inflection; Khoirao language; Noun; Verb